2010
DOI: 10.1002/chem.200902558
|View full text |Cite
|
Sign up to set email alerts
|

Additive Tuning of Redox Potential in Metallacarboranes by Sequential Halogen Substitution

Abstract: The first artificially made set of electron acceptors is presented that are derived from a unique platform Cs[3,3'-Co(C(2)B(9)H(11))(2)], for which the redox potential of each differs from its predecessor by a fixed amount. The sequence of electron acceptors is made by substituting one, two, or more hydrogen atoms by chlorine atoms, yielding Cs[3,3'-Co(C(2)B(9)H(11-y)Cl(y))(C(2)B(9)H(11-z)Cl(z))]. The higher the number of chlorine substituents, the more prone the platform is to be reduced. The effect is comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…The high stability of these anions enable to run MALDI-TOF-MS experiments avoiding the use of a matrix, and this is most probably the reason for the direct relationship between the peak intensity and the molar fraction. 10 As clusters have the same number of boron atoms (18), the molecular peaks roughly show a similar envelope shape, just modulated by the number of chlorine substituents that are influenced by two isotopes: 35 Cl (76%) and 37 Cl (24%). Thus, the integral of the area under the multiplets is used to estimate the composition of each mixture directly from the spectra (see Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The high stability of these anions enable to run MALDI-TOF-MS experiments avoiding the use of a matrix, and this is most probably the reason for the direct relationship between the peak intensity and the molar fraction. 10 As clusters have the same number of boron atoms (18), the molecular peaks roughly show a similar envelope shape, just modulated by the number of chlorine substituents that are influenced by two isotopes: 35 Cl (76%) and 37 Cl (24%). Thus, the integral of the area under the multiplets is used to estimate the composition of each mixture directly from the spectra (see Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 95%
“…This allows for incorporation of variety of metals with different properties into nucleic acids and their components. An additional advantage of metallacarboranes is susceptibility to redox potential tuning via particular derivatization of the boron cluster ligands (González-Cardoso et al, 2010;Grimes, 1982). The metallacarboranes have been applied for modification of target ssDNA (Ziółkowski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…With these results in hand other tests were carried out to isolate I 8 - [1] 2À . To this objective, the crude of the reaction between I 8 - [1] À and Na[C 10 H 8 ]w as filtered to remove the existing solid whose IR did not display any BÀHa bsorption. The solvent wase vaporated and the naphthalene was recovered by low-pressuresublimation.…”
Section: Resultsmentioning
confidence: 99%
“…One of the mosto bvious differences between [1] À andf errocene( Fc) is the charge of [1] À ,w hichm akes the lattera nd its congeners some of the few examples of metallocene-type complexes with an egative charge.P revious work has shown that [1] À can be modified by halogenations, [8,9] andi ti saunique framework in its ability to produce as tepwise modulation of its redox potential by each new BÀX( X=halogen) unit added. [10] We recently demonstrated that sequential substitution of BÀHb yB À Xu nits produces an average E 1/2 shift, near 0.13 V, to more positive potential values. [11] This E 1/2 cumulative process is very rare [12] andn o other redox reversible platform seems to be capable of making it as effectively as [1] À .H erein we disclose that 1) the E1 = 2 sitedependence of two opposite effect substituents,I -v ersus Me-, all realized on boron atoms;2 )the power of the E1 = 2 site dependence shift;a nd 3) the application of these concepts to stabilizet he [Co(C 2 B 9 H 11 ) 2 ] 2À framework, [1] 2À ,i nw hich the Co is Co 2 + .…”
Section: Introductionmentioning
confidence: 98%